Exogenous lipoid pneumonia masquerading as a pulmonary nodule: a case report - Shen, Yao; Yao, Su (Frontiers in Medicine, 2026)
This case report describes a patient with exogenous lipoid pneumonia (ELP) presenting as a solitary pulmonary nodule. ELP is a rare chronic pulmonary disorder characterized by nonspecific clinical symptoms and imaging findings. When manifesting as a mass or nodule, features such as lobulation and spiculation on imaging can closely resemble lung cancer, frequently leading to misdiagnosis and unnecessary surgical intervention. We present a retrospective analysis of a pathologically confirmed case of ELP to improve recognition of this condition among both clinicians and pathologists.